Halal Tourism: A Proposed Sharia Model for Implementation - Manan, Abdul; Wirianto, Dicky; Fadhilah, Muhammad Arif; Kamarullah, Kamarullah (Jurnal Ilmiah Peuradeun, 2023)
This qualitative study explored the proper and feasible Halal Tourism (HT) model regarding the implementation of Sharia law in Aceh Province, Indonesia. Observation, questionnaire, and interview were conducted at three important tourist cities in Aceh: Banda Aceh, Sabang, and Takengon. Three hundred twenty-five respondents participated in this research, and convenience sampling was used to select them. The results were analyzed using Miles and Huberman’s qualitative analysis method and the SWOT analysis to construct the expected model. The result indicated that the HT model must be arranged under the following six principles: ease, reliability, safety, trust, openness, and continual improvement. Those principles can be implemented in every aspect of tourism: policies and regulations, facilities, hotels, other accommodations, transportation, and human resources. Also, progress in the HT management must focus on implementing Sharia in the plenary (kaffah) and improving the locals’ prosperity. Besides, the HT model consists of planning, decision-making, providing support, socializing, implementing, and supervising, considering its principles toward tourism and local cultures and values. The implementation of the model is expected to ensure the communities' life and integrate their inextricable foundation, Sharia while stimulating their socio-economic through the possibility of investment and employment in the future.